Review: Eksplorasi Keterkaitan Vertikal Antara Aktivitas Departemen SDM-Strategi SDM Perusahaan - Latisya, Silva (Pusat Pengembangan Kompetensi Aparatur Perdagangan, 2019)
This study aims to explore the vertical alignments between HR department activities and the company's HR strategy. The goal of this study is to ensure how HR activities can be aligned with HR strategies to enhance the HR department works in the context of achieving company goals. The study was conducted by depth discussion of scientific journals that have been written with interactive group brainstorming approach, consisting of 21 students into three groups to discuss and generate ideas about HR activities and their strategic relationships while researchers guide and provide the materialsneeded. The group identified and agreed on seven HR activities including job design; mobilization; selection; retention and separation; performance management; employee training; and compensation, and aligned with each of the four HR strategies identified including the Bargain Laborer; Free Agent; Loyal Soldier; and Committed Expert. The results of the study revealed the relevance of the activities of the HR department with the company's HR strategy. Total organizational performance also be positively influenced by HR activities through the company's HR strategy